(3eONd Edi EOGQI GdafGOb (B/s - (3GdWGFj, MejO YHO GdfHjs ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2006)
(3GdJQGHW Hjf UfGYJj GdSjGMI h GdVjGaI, echfGJ UfGYI GdVjGaI, eaghe GOGQI GdafGOb h GdGJLGgGJ GdMOjKI aj UfGYI GdafGOb, SeGJ GdNOeI GdafObjI h eSJhjGJgG h GdGSJQGJjLjGJ GdGOGQjI GdeWHbI aj UfGYI GdafGOb, JUfjaGJ GdafGOb h GdgjGcd GdJfXjejI dgG, GdGbSGe GdQFjSjI ddGOGQGJ aj GdafGOb, EOGQI GdehGQO GdHTQjI aj GdafGOb h bjGS GdGOGA ajgG, EOGQI GdeQOhO aj UfGYI GdafGOb h CNjQG JcfhdhLjG GdeYdheGJ aj UfGYI GdVjGaIs
(3bGFeI GdLOGhd U(B.13(3; bGFeI GdCTcGd U(B.15 (3HHdjhZQGajG(B: (3U(B.356-365s
Keywords: (3GdGOGQIs; (3GdafGOb `` GOGQIs